Implementasi Manajemen Risiko pada Usaha Mikro Kecil dan Menengah (UMKM) - Novi Aisha (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are highly vulnerable to a wide range of business risks that may threaten their operational continuity and long-term sustainability. These risks include financial instability, market fluctuations, supply chain disruptions, regulatory changes, and limited managerial capacity. This study aims to describe the implementation of risk management practices in MSMEs by examining the processes of risk identification, analysis, evaluation, and control in accordance with the specific characteristics and limitations of MSME operations. The research applies a qualitative method using a document study approach to explore and analyze the phenomenon of risk management within MSMEs. The data utilized consist of secondary sources, including scholarly journal articles, previous empirical research findings, official publications from relevant institutions, government reports, and other publicly accessible documents related to MSME development. The findings reveal that although MSME actors generally recognize the existence of various business risks, the practical implementation of structured and systematic risk management remains suboptimal. Many MSMEs still apply informal, reactive, and experience-based strategies rather than comprehensive risk management frameworks, indicating the need for improved awareness, training, and institutional support.